Persistent opioid use is associated with worse survival after lobectomy for stage I non-small cell lung cancer. Issue 10 (October 2019) - Nelson, David B.; Cata, Juan P.; Niu, Jiangong; Mitchell, Kyle G.; Vaporciyan, Ara A.; Antonoff, Mara B.; Hofstetter, Wayne L.; Giordano, Sharon H.; Sepesi, Boris; Mehran, Reza J.; Rice, David C.
Abstract : Abstract: The incidence of persistent opioid use after lung surgery is high. Although adverse effects by opioids have been well described, it is unknown whether persistent opioid use is associated with worse survival. Patients who received a lobectomy for stage I NSCLC from 2007 to 2013 were identified from the Surveillance, Epidemiology and End Results-Medicare database. Opioid use was ascertained through records of prescriptions filled through part D. Patients were matched 2:1 according to their likelihood of persistent opioid use, which was defined as any opioid prescription filled 3 to 6 months after surgery. Two thousand eight hundred eighty-four patients were identified. The incidence of persistent opioid use 3 to 6 months after surgery was 27.0%. After matching, persistent opioid use was associated with worse overall survival ( P < 0.001) and cancer-specific survival ( P < 0.001). Those who used the lowest quartile of opioids, which was often manifested as a single opioid prescription, showed similar overall survival as no opioid use (HR 1.27, 95% confidence interval [CI] 0.93-1.72). However, the second and third quartiles of opioid use were associated with decreased overall survival (HR 1.53, 95% CI 1.14-2.03 and HR 1.39, 95% CI 1.04-1.86, respectively) that was nonetheless less severe than the highest quartile of opioid use (HR 2.50, 95% CI 1.95-3.21). Age, sex, marital status, comorbidity, tumor size, tumor grade, and radiation were also associated with worse overall survival, with chemotherapy use and video-assisted thoracoscopic surgery being associated with improved overall survival. Persistent opioid use 3 to 6 months after lobectomy is independently associated with worse overall survival and worse cancer-specific survival. Abstract : Supplemental Digital Content is Available in the Text.Persistent opioid use 3 to 6 months after lobectomy for stage I non-small cell lung cancer is associated with worse overall survival and cancer specific survival.